Antimicrobial Properties of Snail Slime (Achatina Fulica) on the Growth of Actinobacilus Actinomycetemcomitans Bacteria Causing Periodontitis - I Gusti Agung Ayu Putu Swastini (Journal of Global Pharma Technology, 2016)
Aim: The purpose of this study was to calculate the inhibition zones of the growth of A. actinomycetemcomitans by snail slime at concentrations of 12.5%, 25%, 50%, 100%. Methods: The study was an experimental randomized posttest-only control group design. This research was conducted in the oral biology laboratory of the Faculty of Dentistry, Airlangga University, Surabaya Indonesia. Variables in this study snail slime were made with concentrations of 12.5%, 25%, 50% and 100%. Take germ stock with osse, then plant on BHI broth media, then incubate 37C for 24 hours. Plant germs on BHI media so that with the swab technique to evenly spread on the surface, then contact the paper disc that has been given each concentration of 12,%, 25%, 50%, 100%, with tweezers on the surface as much as 10 micromillimeters, then incubate 37C for 2x 24 hours, eight repetitions are carried out. Results: The mean diameter of the inhibitory zone snail slime on the growth of A. actinomycetemcomitans bacteria in the treatment groups had significant differences p<0.05. The mean inhibition zone between controls and LB treatment group (LB 12.5%, 25%, 50%, 100%), were statistically different (p<0.05).In contrast with LB 12.5% (p>0.05) which significant difference with the control group. Conclusion: The concentration of 100% snail slime has the highest inhibitory power, against the growth of the A. actinomycetemcomitans bacteria, The 12.5% concentration snail slime showed no antibacterial activity against the growth A. actinomycetemcomitans.Keywords: Snail slime, Actinobacilus actinomycetemcomitans bacteria, Inhibition zone diameter.